Association of THBS1 genetic variants and mRNA expression with the risks of ischemic stroke and long-term death after stroke - Chen, Changying; Chen, Xuemei; Yang, Siyuan; Li, Qingqing; Ren, Zhanyun; Wang, Lu; Jiang, Yuzhang; Gu, Xincheng; Liu, Fangyuan; Mu, Jialing; Liu, Lihua; Wang, Yi; et al. (Frontiers in Aging Neuroscience, 2022)
Background Thrombospondin-1 (THBS1) derived from platelets and acted as a critical mediator of hemostasis promoting platelet activation in thrombus formation. The biological connection of genetic variants and mRNA expression of THBS1 with ischemic stroke (IS) warrants further validation with population-based evidence. Objective To evaluate the association of single nucleotide polymorphisms (SNPs) and mRNA expression of THBS1 with the risks of IS and long-term death after stroke. Methods A case-control study consisted of 4,584 IS patients recruited from five hospitals in Jiangsu, China, and 4,663 age-gender-matched controls free of IS. A cohort study enrolled 4,098 participants free of stroke and lasted from 2009 to 2022. Early collected 3158 IS patients aged between 35 and 80 years were followed up an average of 5.86-year to follow up their long-term death outcomes. Two tagSNPs of the THBS1 gene, rs2236471 and rs3743125, were genotyped in all subjects and THBS1 mRNA expression of peripheral leukocyte was measured using RT-qPCR in 314 IS cases and 314 controls. Results There is no significant difference in genotype and haplotype frequencies of rs2236741 and rs3743125 between IS cases and controls (all P > 0.05). Furthermore, the cohort studies did not observe significant associations between THBS1 variants and the risk of IS incidence or long-term death after IS (all P > 0.05). The THBS1 mRNA expression level (2–ΔΔCT) in IS cases was approximately equal to that in controls (1.01 vs. 0.99, P = 0.833). In addition, THBS1 mRNA expression had no significant association with all-cause death, stroke death, and IS death of IS patients (all P > 0.05). Conclusion Therefore, our study suggested that there is no significant association of THBS1 polymorphisms and mRNA expression level with the risk of IS and long-term death after IS.